B-value definition in Galvele's pit model. (February 2023) - Wang, Ke; Li, Tianshu; Salasi, Mobin; Frankel, Gerald S.; Calo, Victor; Iannuzzi, Mariano
Abstract: We use one-dimensional mass transport models to investigate the chloride concentration effect on the potential drop inside a pit cavity. Galvele's pitting model predicts a B value of 59 mV, independent of the complexation reactions and concentration-dependent diffusivity when ions can migrate freely. Higher B values (>59 mV) at 25 °C are commonly attributed to ion interactions in the pit solution, also explaining the material and electrolyte effect on the B value in Galvele's pit model. Our analysis suggests that practical pitting corrosion models require a comprehensive mass transport component that includes multi-species interactions.